Impact of Left Atrial Bipolar Electrogram Voltage on First Pass Pulmonary Vein Isolation During Radiofrequency Catheter Ablation - Garg, Lohit; Pothineni, Naga Venkata K.; Daw, J. Michael; Hyman, Matthew C.; Arkles, Jeffrey; Tschabrunn, Cory M.; Santangeli, Pasquale; Marchlinski, Francis E. (Frontiers in Physiology, 2020)
Background First pass pulmonary vein isolation (PVI) is associated with durable isolation and reduced recurrence of atrial fibrillation (AF). Objective We sought to investigate the relationship between left atrial electrogram voltage using multielectrode fast automated mapping (ME-FAM) and first pass isolation with radiofrequency ablation. Methods We included consecutive patients (pts) undergoing first time ablation for paroxysmal AF (pAF), and compared the voltage characteristics between patients with and without first pass isolation. Left atrium (LA) adjacent to PVs was divided into 6 regions, and mean voltages obtained with ME-FAM (Pentaray, Biosense Webster) in each region and compared. LA electrograms with marked low voltage (<0.5 mV) were identified and the voltage characteristics at the site of difficult isolation was compared to the voltage in adjacent region. Results Twenty consecutive patients (10 with first pass and 10 without) with a mean age of 63.3 ± 6.2 years, 65% males, were studied. Difficult isolation occurred on the right PVs in eight pts and left PVs in three pts. The mean voltage in pts without first pass isolation was lower in all 6 regions; posterior wall (1.93 ± 1.46 versus 2.99 ± 2.19; p < 0.001), roof (1.83 ± 2.29 versus 2.47 ± 1.99; p < 0.001), LA-LPV posterior (1.85 ± 3.09 versus 2.99 ± 2.19, p < 0.001), LA-LPV ridge (1.42 ± 1.04 versus 1.91 ± 1.61; p < 0.001), LA-RPV posterior (1.51 ± 1.11 versus 2.30 ± 1.77, p < 0.001) and LA-RPV septum (1.55 ± 1.23 versus 2.31 ± 1.40, p < 0.001). Patients without first pass isolation also had a larger percentage of signal with an amplitude of <0.5 mV for each of the six regions (12.8% versus 7.5%). In addition, the mean voltage at the site of difficult isolation was lower at 8 out of 11 sites compared to mean voltage for remaining electrograms in that region. Conclusion In patients undergoing PVI for paroxysmal AF, failure in first pass isolation was associated with lower global LA voltage, more marked low amplitude signal (<0.5 mV) and lower local signal voltage at the site with difficult isolation. The results suggest that a greater degree of global and segmental fibrosis may play a role in ease of PV isolation with radiofrequency energy.